Deus acima de todos e todos under his eye: espectros do patriarcado na série The Handmaid’s Tale e o contexto sóciopolítico brasileiro - Duarte, Vlamir Marques (2021)
The importance of audiovisual works and their symbologies about reality reveal representations of today's society, fostering discussions and reflections on how we organize ourselves as subjects in a social body. Through the fictional series The Handmaid's Tale we seek to bring to light, through the implications between characters and current affairs, the relevance of the discussion of issues of gender and sexuality, especially social meanings of masculinities in Brazil's contemporary setting, with a focus on patriarchal conservatism and fascism in national politics. Our work is supported b y theoretical contributions of assumptions of the social construction of masculinity ( Connell and Pearse, 2015), masculine types (Moore and Gillette, 1993 ), homosociality (Welzer Lang, 2001), among others. The AFCNS method (Film Comprehensive Analysis of t he Serial Narrative), developed by Azubel (2018), instrumentalized the realization of our research. We conclude presenting the intercessions between the series and the current Brazilian political situation, pointing out the ongoing transformations in the relations between genders and proposing media educational possibilities.